DISASTER RECOVERY PLAN JARINGAN DENGAN SISTEM BACKUP OTOMATIS MIKROTIK MENGGUNAKAN METODE FILE TRANSFER PROTOCOL (FTP) PADA JARINGAN WAN PT. INDOTRANS DATA - Numan Musyaffa; Ricki Sastra; Arfhan Prasetyo (Universitas Bina Sarana Informatika, 2020)
Abstract— The need for communication today is very important along with advances in data communication technology found on the internet network, the router as a device that should be able to serve the availability of 24-hour internet network without stopping will have a big impact if a router device experiences damage that can not be predicted, Disaster Recovery Plan is an effort to prevent the risk of attack, or due to the occurrence of disasters, especially to ensure business processes and implementation can continue in an emergency. PT Indotrans Data, an ISP provider company that uses a proxy router device to smoothly exchange communications and data on the internet network, but in backing up the proxy router configuration is still done manually and backup files are stored on internal storage or disks on the proxy router, the system is very ineffective because the backup configuration is not scheduled and the backup file will be lost when the proxy router is damaged, error or reset. A system is needed to implement fast and effective anticipation or handling of network problems on the proxy router and keep backup files or documentation stored properly and safely. Mikrotik configuration automatic backup system with File Transfer Protocol (FTP) method is very precise and effective, because in the backup configuration on the proxy router automatically and scheduled, then the backup file is sent to the Linux server by FTP method automatically every day. Features used in backing up automatic and scheduled Mikrotik configurations using the script tool and proxy scheduler. The Linux server uses the Linux centos operating system and retrieves backup files from the proxy router to the Linux server using the FTP method. Key : Backup , Disaster, FTP, Mikrotik, Router